Quantum oscillations between close-lying states mediated by the electronic continuum in intense high-frequency pulses - Demekhin, Philipp V.; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2015)
The dynamics of neighboring states exposed to short intense laser pulses of carrier frequencies well above the ionization threshold of the system is investigated theoretically in the dipole approximation. It is shown that the ionizing pulse induces a time-dependent non-Hermitian coupling between these states determined by the Raman coupling and the direct ionization probability. This coupling induces quantum oscillations between the neighboring states while the strong pulse is on. The phenomenon opens the possibility to achieve a coherent control over the populations of neighboring states by short intense ionizing pulses. The present numerical results suggest exciting applications for free-electron lasers and attosecond experiments.
Gesehen am 12.01.2021